Cooperative Bond Activation and Facile Intramolecular Aryl Transfer of Nickel–Aluminum Pincer‐type Complexes. Issue 27 (1st June 2021) - Graziano, Brendan J.; Vollmer, Matthew V.; Lu, Connie C.
Abstract: Pincer‐type nickel–aluminum complexes were synthesized using two equivalents of the phosphinoamide, [PhNCH2 P i Pr2 ] − . The Ni 0 –Al III complexes, ( Mes PAlP)Ni2 (μ‐N2 ) and ( Mes PAlP)Ni2 (μ‐COD), where Mes PAlP is (Mes)Al(NPhCH2 P i Pr2 )2, were structurally characterized. The (PAlP)Ni system exhibited cooperative bond cleavage mediated by the two‐site Ni–Al unit, including oxidative addition of aryl halides, H2 activation, and ortho‐directed C−H bond activation of pyridine N‐oxide. One intriguing reaction is the reversible intramolecular transfer of the mesityl ring from the Al to the Ni site, which is evocative of the transmetalation step during cross‐coupling catalysis. The aryl‐transfer product, (THF)Al(NPhCH2 P i Pr2 )2 Ni(Mes), is the first example of a first‐row transition metal–aluminyl pincer complex. The addition of a judicious donor enables the Al metalloligand to convert reversibly between the alane and aluminyl forms via aryl group transfer to and from Ni, respectively. Theoretical calculations support a zwitterionic Ni δ− –Al δ+ electronic structure in the nickel–aluminyl complex. Abstract : Nickel complexes supported by a pincer‐type aluminum metalloligand were synthesized and demonstrated several unique modes of metal–ligand cooperativity. Unexpectedly, the PAlP framework reversibly converts between the alane and aluminyl through aryl group transmetalation between aluminum and nickel.